2017
DOI: 10.7150/jca.17295
|View full text |Cite
|
Sign up to set email alerts
|

HOXA5 and p53 cooperate to suppress lung cancer cell invasion and serve as good prognostic factors in non-small cell lung cancer

Abstract: Lung cancer is the leading cause of cancer mortality worldwide and tumor metastasis is the major cause of cancer-related death. Our previous study suggested that Homeobox A5 (HOXA5) could inhibit lung cancer cell invasion via regulating cytoskeletal remodeling and involved in tumor metastasis. Recently, consensus HOX binding sites was found in the p53 gene promoter region. However, whether the HOXA5 could cooperate with p53 and contribute the inhibition of lung cancer cell invasion is still unclear. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…In solid malignancies such as breast carcinoma, HOXA5 functions as a positive regulator of TP53, and loss of HOXA5 expression results in failure to block malignant transformation of epithelial cells (Raman et al 2000;Chen et al 2004). Similar findings of HOXA5 inducing apoptosis and a better clinical outcome have been observed in lung carcinoma (Chang et al 2017) and liposarcoma (Lee et al 2015). This previously described cooperative axis of HOXA5 and TP53 suppressing cellular proliferation in human carcinoma and liposarcoma is the inverse effect of what we observed in glioblastomas, where HOXA5 promotes cellular proliferation and inhibits TP53 expression.…”
Section: Discussionmentioning
confidence: 55%
“…In solid malignancies such as breast carcinoma, HOXA5 functions as a positive regulator of TP53, and loss of HOXA5 expression results in failure to block malignant transformation of epithelial cells (Raman et al 2000;Chen et al 2004). Similar findings of HOXA5 inducing apoptosis and a better clinical outcome have been observed in lung carcinoma (Chang et al 2017) and liposarcoma (Lee et al 2015). This previously described cooperative axis of HOXA5 and TP53 suppressing cellular proliferation in human carcinoma and liposarcoma is the inverse effect of what we observed in glioblastomas, where HOXA5 promotes cellular proliferation and inhibits TP53 expression.…”
Section: Discussionmentioning
confidence: 55%
“…Here, we revealed that Hoxa5 was direct target of miR-19a-3p and contribute to miR-19a-3p-induced BMSC osteogenic differentiation. Hoxa5 was served as tumor suppressor in a number of cancers including non-small cell lung cancer [28], osteosarcoma [29], gastric cancer [30] and gastric cancer [31]. Hoxa5 was also reported to alleviate inflammation and induce adipose tissue browning [32].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cooperation between HOXA5 and p53 is found to be able to inhibit the invasion of tumor cells, at least partially owing to the decrease of MMP2 activity in NSCLC. [56]. Low expression of HOXA5 is associated with high levels of nuclear β-catenin, which is the hallmark of the Wnt signaling pathway in colorectal carcinoma [57].…”
Section: Discussionmentioning
confidence: 99%